Long-term Follow-up of Eosinophilic Granulomas of the Axial and Appendicular Skeleton Managed With Biopsy Alone - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Background: This study aimed to evaluate the long-term clinical and radiologic follow-up results of eosinophilic granulomas (EGs) of the axial and appendicular skeleton managed with biopsy alone. Methods: Fifty-five patients with unifocal osseous EGs of the axial and appendicular skeleton were followed after biopsy. Patients were divided into 2 groups on the basis of localization of the lesions. In group 1, there were 32 (58.2%) children with extremity long bone involvement: femur, tibia, humerus, ulna, and radius. Group 2 included 23 (41.8%) patients with lesions located in other appendicular and axial skeleton bones: pelvis, scapula, clavicle, lumbar, and thoracic vertebrae. After confirming the diagnosis by a closed biopsy, no further surgical intervention was performed. Clinical recovery included regression of the localized symptoms, mainly pain resolution. Functional improvement was assessed by Musculoskeletal Tumor Society (MSTS) scoring. Radiologic healing was defined as ossification of the entire lesion with cortical thickening in long and flat bones, and restoration of vertebral body height in the spine. Complications, including local recurrence, were determined. Results: The patients comprised 28 boys and 27 girls with an average age of 9.2 years (range, 3 to 16 y). The average follow-up was 76 months (range, 28 to 132 mo). The median time from biopsy to clinical recovery was 17 days [95% confidence interval (CI), 13.3-20.6] and 36 days (95% Cl, 32.8-39.1) in group 1 and group 2, respectively. MSTS scores increased progressively till the end of 12 months in both groups. The median time from biopsy to radiologic healing was 16 months (95% CI, 11.5-20.4) and 42 months (95% Cl, 39.3-44.6) in group 1 and group 2, respectively. Both clinical recovery (P=0.021) and radiologic healing (P=0.009) were significantly faster in group 1 compared with group 2. No major complication was seen after biopsy. All lesions regressed without a local recurrence. Conclusions: Unifocal osseous EGs have spontaneous healing potential and confirming the diagnosis by biopsy is enough to obtain good clinical and radiologic results without any additional surgical intervention. Type of Study: This was a therapeutic study.
Keywords: Langerhans cell histiocytosis; eosinophilic granuloma; extremities; spine; biopsy; LANGERHANS-CELL HISTIOCYTOSIS; BONE; SYSTEM; ORBIT